First report of the genus Rhicnogryllus Chopard, 1925 (Orthoptera: Trigonidiidae; Trigonidiinae) in China with description of a new species - He, Zhixin; Ma, Ge; Zhang, Tao; Ma, Libin (Zootaxa, 2021)
A new species, Rhicnogryllus nanlingensis sp. n., was reported from Guangdong, China. This was the first time of Rhicnogryllus was recorded from China. Description and illustrations for the new species were provided.